Impedance control finishing with compliant manipulator - Steven (2017)
Collaborative robots or cobots have been a trend in robotics industry. It is shown that the collaboration between human and robot would improve the productivity and quality of products. Such possibility can be adopted on surface finishing process, as human tend to be inaccurate and inconsistent. Good quality of surface finishing requires accurate control of material removal rate, which depends on various parameters, such as abrasive tools used, contact force between tools as well as grinding speed. In general, there are two types of control strategies have been implemented in todays automated machining and repair process, that is position and force control. However, these strategies are often inadequate for finesse finishing operations or unstable tasks such as edge grinding and profiling. Besides position and force, stiffness (or compliance) and damping is another key factor required in finishing process, which known as impedance control. The impedance control mode of the robot (specifically on KUKA iiwa-Lbr) allows the stiffness and damping to be modulated. This project aims to study and develop various path planning method by utilising various programming software on compliant robot in autonomous way. Selecting different path may be challenging as there exist limits to the robot’s motion and orientations of end tool. In addition, this project also cover part of analysis on different parameters affecting surface finishing process, such as grinding speed, stiffness values and contact force generated. This project is a joint lab programme established between Nanyang Technological University (NTU) and Rolls-Royce (RR), under an official name of Rolls-Royce@NTU Corporate Lab